Cost of illness of HER2-positive and metastatic and recurrent HER2-positive breast cancer - a Danish register-based study from 2005 to 2016 - M. Spanggaard; J. Olsen; K. F. Jensen; M. Anderson (BMC, 2022)
Abstract Background Information and knowledge about cost of illness and labour productivity in patients with HER2-positive early-stage and metastatic breast cancer treated with trastuzumab is limited. The aim of this study was to estimate the direct and indirect costs associated with treatment of HER2-positive breast cancer among patients with early-stage and metastatic breast cancer, treated with trastuzumab, in a 10-year period after diagnosis. Materials and methods This study included all Danish HER2-positive breast cancer patients (≥ 18 years) treated with trastuzumab between 2005 and 2016 identified in The Danish Patient Register and the Danish Cancer Register. Furthermore, we identified patients experiencing metastatic or recurrent breast cancer. For the study populations, we estimated total direct costs and indirect costs for one year prior to the breast cancer diagnosis and up to 10 years after diagnosis compared with a group of matched controls free of breast cancer. In addition to The Danish Patient Register and Cancer Register, we applied patient level data from The Civil Registration System, The National Pathology Register, National Health Service Register for Primary Care, Register of Medicinal Product Statistics, Register of Municipal Services, The DREAM database, and Population's Education Register. Results We identified 4,153 HER2-positive breast cancer patients, whereof 27% were identified with metastatic or recurrent breast cancer. During the follow-up period of 10 years, we estimated excess direct costs of EUR 115,000 among the total study population compared to controls; EUR 211,000 among patients with metastases or recurrence; and EUR 89,000 among patients without metastases or recurrence. Direct costs were found to be highest in the first year after diagnosis and also peaked in the year after recurrence. Labour productivity was significantly lower among patients with recurrence 10 years after breast cancer diagnosis compared with controls. Conclusions In this study, we estimated the direct and indirect cost associated with HER2-positive breast cancer. The costs were significantly higher during the 10 years after diagnosis compared to the control group, specifically among patients experiencing metastases or recurrence of breast cancer.